African-American Youth and Exposure to Community Violence: Supporting Change from the Inside - Anita Jones Thomas; Devin Carey; Kia-Rai Prewitt; Edna Romero; Maryse Richards; Barbara Velsor-Friedrich (Journal for Social Action in Counseling and Psychology)
Children’s exposure to community violence and its effects on child health outcomes have become a major public health concern in this country, and African-American youth are at greatest risk. Participatory action research, as a vehicle for promoting social justice, is one tool that can be used to address community violence. This article describes the use of focus groups as a way to give African-American youth a voice in providing solutions to violence exposure through the revision of curricula (coping skills and civic engagement). Participants reported a variety of stressors, including exposure to violence, and a lack of coping strategies and adult support for processing violence. Suggestions for curriculum revisions are included. The process of conducting groups, lessons learned from the process, and implications for researchers interested in promoting social justice are discussed.